Research on the Development of TCM Tourism in Western Anhui Region from the Perspective of Industrial Integration - Wang, Mengjie (Pacific International Journal, 2026)
The western Anhui region has prominent advantages in traditional Chinese medicine tourism resources, with favorable policy advantages, TCM resource advantages and tourism resource advantages. This research is based on the dual national strategic background of “Healthy China” and “Rural Revitalization”. It conforms to the trend of cultural tourism consumption upgrading and industrial integration, which focuses on the development of TCM tourism in the region from the perspective of industrial integration. This paper employs literature review, field research, case analysis, and SWOT analysis to synthesize relevant academic research over the past five years. It systematically examines the current development status, resource endowment, challenges, and optimization pathways for TCM tourism in the region. The conclusion indicates that to realize the region’s significant potential in this sector, deeper industrial integration is demanded, along with coordinated enhancements to the product system, brand building, infrastructure, and services. This paper aims to enrich the application of industrial integration theory in regional TCM tourism, providing a theoretical reference for similar areas. Furthermore, it seeks to provide a pathway for the region to facilitate economic transformation, inherit TCM culture, consolidate poverty alleviation achievements, and realize rural revitalization.